Characterization of novel natural cellulosic fibers from Abutilon Indicum for potential reinforcement in polymer composites. Issue 1 (7th October 2022) - ArunRamnath, R.; Murugan, S.; Sanjay, M. R.; Vinod, A.; Indran, S.; Elnaggar, Ashraf Y.; Fallatah, Ahmed M.; Siengchin, Suchart
Abstract: The prime objective of this research study was the investigation the new natural cellulosic fiber extracted from the stem of Abutilon Indicum plants as an alternative reinforcement in greener composite materials for structural applications. Abutilon Indicum a flowering plant with unique medicinal values are abundantly found in India and other south Asian countries. The fibers extracted from the stem of the Abutilon Indicum plant are proven to be sustainable, ecofriendly, and novel and hence this fiber is chosen for characterization study. In this experimental investigation the physical, chemical, thermal, morphological, crystallinity, chemical constituents, and surface characteristics of raw Abutilon Indicum fibers (AIF) were analyzed. Chemical analysis results convey the presence of higher cellulose content of (56.12 wt.%) in AIF. The diameter (175 μm) and density (1.170 g/cm 3 ) of AIFs are determined by physical analysis of the raw fibers. Such lower density values observed in AIF make it as a perfect material for lightweight applications. Crystalline properties of AIFs are determined from X‐ray diffraction tests with a crystalline index of 77.35%, and crystalline size of 2.20 nm, which attributes to the presence of cellulose‐1 β and the crystallites are ordered in nature. Thermal stability of 175°C, maximum degradation temperature upto 302.6°C and kinetic activation energy of 86.95 kJ/mol of AIF are established based on thermo gravimetric analysis. Morphological and surface characteristics of AIF through a scanning electron microscope (SEM) and atomic force microscope (AFM) analysis revealed that the raw fibers display a relatively finer surface. Research findings of the AIF mentioned above conclude that the AIFs prove to be an ideal, alternative reinforcement in greener composite materials for sustainable and cleaner production of components in structural applications.